Prophets of the great spirit : Native American revitalization movements in eastern North America - Cave, Alfred A. (University of Nebraska Press, 2006)
Prophets of the Great Spirit offers an in-depth look at the work of a diverse group of Native American visionaries who forged new, syncretic religious movements that provided their peoples with the ideological means to resist white domination. By blending ideas borrowed from Christianity with traditional beliefs, they transformed "high" gods or a distant and aloof creator into a powerful, activist deity that came to be called the Great Spirit. These revitalization leaders sought to regain the favor of the Great Spirit through reforms within their societies and the inauguration of new ritual practices